Ethical behavior perceptions in Russia: Do ethics‐related programs and individual characteristics matter?. Issue 4 (5th June 2021) - Ermasova, Natalia; Ermasova, Polina
Abstract: This paper aims to analyze how individual differences and ethics‐related programs predict Russian business students and working adults' perception of personal business ethics. This research evaluates the business ethics perceptions based on surveys of 1, 207 managers, employees, and business students in Russia. This study finds the significant correlations between individual differences (gender, age, education level, and management experience), ethics‐related programs (business ethics courses taught in universities, ethics and diversity professional development training), and personal business ethics' perceptions of Russian business students and working adults. We also find that individual differences moderate the relationship between ethics‐related programs and how the personal business ethics of Russian business students and working adults are perceived. These findings advance current literature by revealing that age moderates the relationship between ethics‐related programs (formal ethic courses, ethics, and diversity trainings) and personal ethical behavior perceptions of working adults and business students in Russia. Our study found that gender had a significant positive moderating effect on relationship of organizational code of ethics, formal ethic courses, and diversity professional development with personal ethical behavior perceptions. The relation between personal ethical behavior perceptions and the presence of an organizational code of ethics was negative and marginally moderated by age and managerial experience. This study contributes to business ethics research by deepening the understanding of the impact of individual differences on the relationship between ethics‐related programs and personal business ethics' perceptions.